P147 Do IBD Patient Treatment Outcomes Expectations Differ by Ethnicity and Gender?. (21st January 2022) - Broide, E; Richter, V; Mari, A; Khoury, T; Shirin, H; Naftali, T
Abstract: Background: Understanding IBD Patient's expectations of treatments outcomes may improve understanding of patient's needs. These expectations may differ in different ethnic groups. Awareness of the patient's expectations and preferences will decrease the gap between patients and physicians. We aimed to investigate patient's preferences and priorities for treatment outcomes among Jewish and Muslim IBD patients in Israel. Methods: A prospective survey of Muslim IBD patients was compared to historical data of Jewish IBD patients. Data included demographics, socioeconomics, and disease parameters. Patients were asked to rank ten items regarding their preferences for treatment outcome, based on the ten IBD disk items. Results: 121 Muslim patients were compared to 240 Jewish patients. Both groups were equal regarding age and IBD type (Crohn's or ulcerative colitis). The Jewish IBD patients were characterized by including more female (p<0.001), higher education level (p=0.02), more urban residence (p<0.001), less unemployment (p=0.012), higher income level (p<0.001), and less relationship with a partner (p<0.001). Patient's priorities stratified according to the 10 IBD disk items revealed that disease symptoms including abdominal pain, energy, and regular defecation ranked highest in both Muslims and Jews. The scores given by the Muslim patients were significantly lower (range 6.69 - 4.29) than the scores given by the Jewish patients (range: 9.03 – 6.25) regarding all items, except for body image. Jewish women attached higher priority to abdominal pain, energy, education and work, sleep, and joint pain compared to Muslim women. Cluster analysis and multivariable regression analysis revealed that factors associated with higher patients' preferences (cluster 2) were Jewish religion [OR, 4.77; 95% CI, 2.36–9.61, p<0.001], and disease activity [1–2 attacks: OR, 2.13; 95% CI, 1.02–4.45, p=0.043; primarily active disease: OR, 5.29; 95% CI, 2.30–12.18, p<0.001]. Factors unlikely to be associated with higher patient's preference (cluster 2) were male gender [OR, 0.5; 95% CI, 0.271–0.935, p=0.030], and income level above average [OR, 0.267; 95% CI, 0.124–0.577, p=0.001]. Conclusion: Ethnic, gender, and socioeconomic disparity have a high impact on patient's ranking of priorities for treatment outcome. Despite the ethnic and cultural differences, symptoms relief is in the highest priority in both patient groups. Understanding patient's priorities will improve communication and enable a better personalized approach.